2017
DOI: 10.1515/hf-2017-0040
|View full text |Cite
|
Sign up to set email alerts
|

Water migration in poplar wood during microwave drying studied by time domain nuclear magnetic resonance (TD-NMR)

Abstract: The migration of bound water and free water has been investigated during microwave drying of wood by the time domain nuclear magnetic resonance (TD-NMR) technique. Both the heartwood (hW) and sapwood (sW) of Beijing poplar (Populus beijingensisW. Y. Hsu) and Qingpi poplar (Populus platyphyllaT. Y. Sun) were studied. The microwave drying is characterized by a fast drying rate, and there is a linear relation between moisture content (MC) and microwave drying time (t). The drying rate of free water is about 2.7 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…As a result of this process, in this case, the drying rate is limited by the diffusion process so that further increasing the air flux intensity does not change it. These results allow to rationalize and explain various previous observations ( 1 , 4 , 32 ) on the macroscopic evolutions of bound and free water during drying.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…As a result of this process, in this case, the drying rate is limited by the diffusion process so that further increasing the air flux intensity does not change it. These results allow to rationalize and explain various previous observations ( 1 , 4 , 32 ) on the macroscopic evolutions of bound and free water during drying.…”
Section: Introductionsupporting
confidence: 85%
“…For drying, different phenomena were observed: in some cases, a homogeneous decrease of the water content throughout the medium and, in other cases, a dry front developing from the free surface ( 29 – 32 ). In addition, it was observed that during slow drying, the bound water concentration decreases when most free water has disappeared ( 31 33 ), while for fast drying in hardwood, the bound water content decreases proportionally to the free water content ( 4 ). To explain the latter effect, it was suggested that the free water is extracted by absorption in the cell walls and then transported toward the free surface ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…A homogeneous decrease of the water content throughout the medium was for example observed in some cases whereas a dry front developed from the free surface in other cases [23][24][25][26]. Also, it was observed that during slow drying, bound water concentration decreases when most free water has disappeared [26][27][28] while for fast drying bound water content decreases proportionally to free water content [29].…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation times are differentiated as T 1 (spin-lattice) and T 2 (spin-spin) relaxation. With respect to wood-water interactions, previous LFNMR research has primarily focused on T 2 relaxation (Flibotte et al 1990;Araujo et al 1992;Labbé et al 2002Labbé et al , 2006Elder et al 2006;Thygesen and Elder 2008;Thygesen et al 2010;Telkki et al 2013;Fredriksson and Thygesen 2017;Li et al 2017), while a few studies have employed two-dimensional (2D) T 1 T 2 LFNMR correlation spectroscopy (Cox et al 2010;Bonnet et al 2017), which appears to be an even more powerful method for moisture characterization.…”
Section: Introductionmentioning
confidence: 99%